The Evaluation of the State University Operational Assistance Policy: The Case of the Two State Universities - Hadiansyah, Achmad; Silaban, Himsar; Nenobais, Harry; Arianda, Yoga Dwi (Indonesian Research Journal in Education |IRJE|, 2024)
To maintain the continuity of the teaching and learning process at State Universities by minimum services, in 2021, the government has launched the state universities operational assistance (BOPTN) policy by providing operational funding assistance to state universities. The education budget allocated by the government does not seem to be the operational needs of a state university, especially those in the DKI Jakarta region. Therefore, evaluation of this policy is necessary. The qualitative research method was carried out by using the Dunn's six evaluation criteria, consisting of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This research was conducted at the Universitas Pembangunan Nasional Veteran Jakarta (UPNVJ) and Universitas Negeri Jakarta (UNJ). It indicated that the BOPTN policy was effective, efficient, and appropriate in assisting operations at PTNs in the DKI Jakarta region. However, the amount of assistance provided was still not enough to cover all operational costs, and the amount among PTNs was also not fair, and complaints were still found from students.